Rola ziemiaństwa polskiego w industrializacji Ukrainy w drugiej połowie XIX wieku - Anusik, Aleksandra (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
The article describes impact of Polish landowners on the industrialization of Ukraine in the second half of the 19th century. It briefly discusses the political and economic situation of Ukraine in the very period, main technological factors that influenced industrial development of the region and the capitalist system which became dominant in that time. In the final part of the article chosen representatives of Polish landowners and properties they owned in the Kiev and Podolia Governorate are described. In such a way it is shown whether recent technological inventions and capitalist forms of ownership were really used in the economic practice.